2019
DOI: 10.1515/jcim-2016-0056
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous lymphoid hyperplasia induced by Hirudo medicinalis (leeches)

Abstract: For centuries, Hirudo medicinalis (medicinal leech) has been used as a remedy to treat many discomforts, such as muscle and joint pain. Nowadays, using leech in reconstructive surgery, microsurgery, wound and flap healing, venous insufficiency, varicosities and many other disorders has increased. In this study, we report a 45 year old female patient with six pruritic papules on her legs since10 months ago that appeared about 4 weeks after one session of leech application. Skin biopsy was performed on one of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 9 publications
1
10
0
2
Order By: Relevance
“…Pseudolymphoma at the site of leech therapy is mostly presented in the form of firm, erythematous, brown or purple nodules, or papules; however, the lesions are rarely presented as plaques [ [4][5][6][7][8][9]7,11,10]. Some studies reported pruritus as a symptom of pseudolymphoma following leech therapy [7][8][9][10][11]. In the case of our patient, the lesions were pruritic papules.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…Pseudolymphoma at the site of leech therapy is mostly presented in the form of firm, erythematous, brown or purple nodules, or papules; however, the lesions are rarely presented as plaques [ [4][5][6][7][8][9]7,11,10]. Some studies reported pruritus as a symptom of pseudolymphoma following leech therapy [7][8][9][10][11]. In the case of our patient, the lesions were pruritic papules.…”
Section: Discussionmentioning
confidence: 60%
“…Persistent bite reaction frequently occurs following scabies and less commonly other arthropod bites. Few cases of pseudolymphomatous bite reaction have been reported after medicinal leech therapy [5][6][7][8][9][10][11]. Table 1 summarizes the features of the cases of cutaneous pseudolymphoma after medicinal leech therapy reported in the English language studies indexed in PubMed and Google Scholar.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations